Economic valuation of heritage sites in Singapore : a contingent valuation method - Chua, Celine Fang Ting (2019)
Increasing concerns over the loss of heritage sites to redevelopment (National Heritage Board, 2017) have amplified the need for a reliable method to provide an estimation to the value to these sites as well as their interactions across society. This level of awareness rises in tandem with many factors including previous loss of heritage sites to redevelopment, as exemplified by the exhumation of Bukit Brown cemetery in 2011 (Ng, 2015), as well as the demolishment of Golden Mile Complex and People’s Park Complex (Wong, 2018). Since the state often contributes substantial funds to these heritage sites, there is a need to estimate the value of these nonmarket goods to assess the allocative efficiency of resources. This paper contributes to the economic valuation of heritage sites in Singapore through a double-bounded dichotomous choice Contingent Valuation Method (CVM) study of three distinct heritage sites in Singapore – Haw Par Villa (HPV), Lau Pa Sat (LPS) and former Tanjong Pagar Railway Station (TPRS). The study values Willingness to Pay (WTP) of maintenance and preservation of heritage sites through the Ordered Probit/Logistic Model. The WTP for the average respondent was found to be S$4.10 to S$10.40. In addition, this paper reports the Total Economic Value (TEV) and estimated use and non-use values of the three heritage sites. Non-use preferences were shown to have a more significant effect size on WTP than use preferences. Lastly, this paper applies variance stable rank method to paired comparison responses to obtain scale values and the relative importance of rankings. The results reveal Singapore Botanic Gardens to be ranked as the most valuable and Sri Senpaga Vinayagar Temple as the least valuable relative to the other heritage sites. Furthermore, results from the CVM and paired comparison can be complemented to provide an estimate for the annual value of heritage sites. These results would add to the limited literature on the valuation of heritage sites in Asia. The paper includes the justification of using the double-bounded dichotomous choice Contingent Valuation Method (CVM) and discusses policy implications.